Financial analysis in the production of organic tomato (Solanum Lycopersicum) in the canton of Pedernales. Manabi - Ecuador - Zambrano Barcia, Tyrone Antonio (2021)
A trial was carried out in the cultivation of organic tomato (S. lycopersicum), whose objective was to determine the treatment with the best cost benefit from the financial analysis, the research is experimental, it was developed in two phases, a greenhouse phase where the plants they were developed in a controlled environment up to 45 days and the second phase is transplants to the final field where they will culminate their maturity cycle and cultural work. The evaluated treatments were: T1- Control; T2- 50% soil + 50% compost; T3- 100% compost; T4- Nitrogen + Zeolite; T5- Nitrogen + Phosphorus + Zeolite; T6- Nitrogen + Phosphorous + Potassium + Zeolite; T7- Nitrogen + Phosphorus + Potassium + Boron + Zeolite; the methodology used was the CYMIT financial analysis. The results obtained in this research point to treatment T7 (complete fertilization + zeolite) as the best cost benefit $ 1.83; and the best efficiency, with averages of 98.56% for N, 147.84% for P, 147.84% for K.